The quality of university education in a federal institution: management, identity and scenarios (Olhar de Professor, 2023)
The present study aimed to analyze the perceptions about the quality of university education at a Federal Institution of Higher Education (FIHE) in the Midwest of Brazil, using a qualitative approach through the technique of completing sentences. The 202 research participants were organized into three groups: 23 Administrative Technicians in Education (ATEs), 56 professors and 123 students. Three categories were identified that correspond to the perception of quality in university education: management (75.1%); identity (15.1%); and scenario (9.6%). The predominant indicators came from the academic management subcategory, that the university and its leaders require: quality of university education, commitment to university education, increased practice, and methods to the detriment of theory, support, increased research and projects, connection between the institution, the community and society, university education aimed at the job market and the construction of knowledge in search of shared solutions.
Keywords: Quality of university education.; University management.; Sentence completion techniques.